2014
DOI: 10.1088/0031-9155/59/4/1005
|View full text |Cite
|
Sign up to set email alerts
|

Soft-tissue imaging with C-arm cone-beam CT using statistical reconstruction

Abstract: The potential for statistical image reconstruction methods such as penalized-likelihood (PL) to improve C-arm cone-beam CT (CBCT) soft-tissue visualization for intraoperative imaging over conventional filtered backprojection (FBP) is assessed in this work by making a fair comparison in relation to soft-tissue performance. A prototype mobile C-arm was used to scan anthropomorphic head and abdomen phantoms as well as a cadaveric torso at doses substantially lower than typical values in diagnostic CT, and the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 72 publications
2
69
0
4
Order By: Relevance
“…Previous studies of dental CBCT scanners also found more beam-hardening artefacts in CBCT images than in MSCT images [23,38]. Better correction algorithms and iterative methods for CBCT are currently being investigated to reduce such beamhardening artefacts [52][53][54]. In our study, the CBCT scans also showed more motion artefacts.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies of dental CBCT scanners also found more beam-hardening artefacts in CBCT images than in MSCT images [23,38]. Better correction algorithms and iterative methods for CBCT are currently being investigated to reduce such beamhardening artefacts [52][53][54]. In our study, the CBCT scans also showed more motion artefacts.…”
Section: Discussionsupporting
confidence: 59%
“…18 It has also been noted that if this a priori knowledge is eliminated and the regularizer behaves like conventional rather than edge-preserving smoothing, many of the image quality improvements in iterative reconstruction disappear. 19 A priori knowledge could increase the noise reduction seen here but may also lead to biased images, such as the vanishing effect for very low contrast lesions. Stronger forms of a priori knowledge could be used but may be dangerous because when the a priori knowledge is incorrect, the final images will be further biased.…”
Section: Discussionmentioning
confidence: 94%
“…These values of δ and β served as a fairly general-purpose selection that avoided patchy image noise and preserved spatial resolution. Alternative parameter selection-for example, specifically to enhance soft-tissue imaging performance 37 -is possible and completely compatible the LDP process.…”
Section: C2 Penalized Likelihood (Pl) Iterative Reconstructionmentioning
confidence: 99%